Santa Duck and his merry helpers - Milgrim, David (G.P. Putnam's Sons, 2010)
Every Christmas, Nicholas Duck helps Santa by collecting gift lists, but this year his little brothers and sister create havoc when they try to help, leading Nicholas to contemplate the true meaning of Christmas.